The Effect of Using Powtoon Animation Video Toward Students Writing Achievement on Descriptive Text in MAS Al Manaar Batuhampar - Iink Rahmawani; Melyann Melani; Reflinda Reflinda; Irwandi Irwandi (Pusdikra-Publishing.com, 2024)
This research was conducted due to several problems that found by the researcher. This research was aimed to find out the effect of using powtoon animation video toward students writing achievement on descriptive text. This research was conducted at the tenth grade of Mas Al Manaar Batuhampar. In this study, the researcher used quantitative method with pre-experimental design by comparing the students’ pre-test and post-test scores. To determine the sample, the researcher used total sampling technique because there just only had one class as experimental class. The subject of this study tenth grade that consist of 26 students. The data was analyzed using t-test formula. The result shown that there were significant difference on the students writing achievement after taught used powtoon animation video. The students mean score of the post-test was 78.65, it is bigger than mean score of pre-test was 49.48. The researcher used t-test formula by comparing score of pre-test and post-test through SPSS. Based on the output statistic, the value of Sig (2-tailed) is 0,00 < 0,05. It means that Ha is accepted. It means that the students writing achievement who are taught using powtoon animation video is better than before. In short, powtoon animation video has a significant effect on students’ writing achievement on descriptive text at Mas Al Manaar Batuhampar.